Pathways to Adulthood: A Three-Generation Urban Study, 1960-1994: (Baltimore, Maryland) - Hardy, Janet B. ([Verlag nicht ermittelbar], 1999)
This collection incorporates both prospective and retrospective data on three generations of families initially living in inner-city Baltimore, Maryland. The prospective data were selected from data collected as part of the Johns Hopkins Collaborative Perinatal Study (JHCPS), a survey of pregnant women seeking prenatal care and delivery at Johns Hopkins Hospital during 1960-1964. JHCPS studied these women (the first-generation mothers, abbreviated as G1) and the children born to them during 1960-1965 (the second-generation children, abbreviated as G2) until the children were 8 years old. The retrospective data come from a follow-up study, conducted in 1992-1994, of G1, G2, and the children born to G2 (the third-generation children, abbreviated as G3). Data from JHCPS on G1 include obstetrical and reproductive history at registration for prenatal care, sociological/family history variables at or around delivery of G2, observations of mother with child when G2 was 4 months old and 8 months old, and family history, demographic, and sociological variables when G2 was age 7. For G2, the data from JHCPS include delivery room observations at birth, pediatric examination data at age 4 months, developmental evaluation data at age 8 months, pediatric-neurological examination data at age 12 months, language, hearing, and speech evaluation summary data at age 36 months, psychological, behavior profile, physical growth, and other tests at age 48 months, psychological, motor, behavior, neurological, vision, physical, and other tests at age 7-1/2 years, and language, hearing, and speech evaluations, physical growth, interval medical history, and other tests at age 8 years. Retrospective data from the follow-up study on G1 include variables on education, employment, family composition, health and health care usage, housing conditions, income and income sources, marital status, partnerships and changes, neighborhood characteristics at registration to JHCPS and current, and reproductive history. For G2, data from the follow-up include information on aspirations, education, schooling, employment, family composition, health and health care usage, housing conditions, income and income sources, legal problems, living arrangements, marriage, partnership and changes, neighborhood characteristics at birth, at ages 11/12 and 16/17, and current, reproductive history, social relationships, smoking, and substance abuse. Data for the assessed third-generation children, i.e., G3s who were 7-8 years old during the follow-up period, include information on cognitive development, academic achievement and behavior, prenatal care, health, day care, and parental aspirations.